Pula - Rojo, Joyce Ann S.
"The influence of popular culture in shaping the concept of female "beauty" has long since been a field of important interest in cultural studies, in particular, that of Sexuality and Gender. Our generation has been bombarded by a host of texts, stories and images delivered to us through different media from the moment we awake until we close our eyes to sleep. These messages have repeated themselves in different forms of communication (radio, tv, cinema, theatre, newspapers) that sometimes we reach the point where we can no longer differentiate what is our inner truth as oppose to the True, Perfect and Beautiful as dictated and propagated by the Media. Pula is a film about a young girl who is desperately trying to fit in to the image of beauty and perfection created by the magazines, tv commercials and tv shows. In her attempt to fit into the standards of Media, she fails to realise the most valuable truth of all: the value of self-worth."